2021
DOI: 10.3233/jad-201392
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Piriform and Bulbar Activity/Excitability/Coupling Upon Amyloid-β Administration in vivo Related to Olfactory Dysfunction

Abstract: Background: Deficits in odor detection and discrimination are premature symptoms of Alzheimer’s disease (AD) that correlate with pathological signs in the olfactory bulb (OB) and piriform cortex (PCx). Similar olfactory dysfunction has been characterized in AD transgenic mice that overproduce amyloid-β (Aβ), which can be prevented by reducing Aβ levels by immunological and pharmacological means, suggesting that olfactory dysfunction depends on Aβ accumulation and Aβ-driven alterations in the OB and/or PCx, as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 105 publications
0
2
0
Order By: Relevance
“…To model amyloid and P-tau pathologies we used ICV injection of Aβ and rTg4510 transgenic mice, respectively (Peña-Ortega, 2013Torres-Flores and Peña-Ortega, 2022;Xolalpa-Cueva et al, 2022). AD-like cognitive alterations induced by ICV administration of Aβ have been previously demonstrated by several groups (Haghani et al, 2012;Peña-Ortega, 2013Eslamizade et al, 2015), including ours (Peña-Ortega, 2013Martínez-García et al, 2021;Torres-Flores and Peña-Ortega, 2022). On the other hand, rTg4510 transgenic mice have been useful to analyze the pathophysiology of tauopathies (Ramsden et al, 2005;SantaCruz et al, 2005;Xolalpa-Cueva et al, 2022) and the interaction between Aβ and P-tau (Busche et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To model amyloid and P-tau pathologies we used ICV injection of Aβ and rTg4510 transgenic mice, respectively (Peña-Ortega, 2013Torres-Flores and Peña-Ortega, 2022;Xolalpa-Cueva et al, 2022). AD-like cognitive alterations induced by ICV administration of Aβ have been previously demonstrated by several groups (Haghani et al, 2012;Peña-Ortega, 2013Eslamizade et al, 2015), including ours (Peña-Ortega, 2013Martínez-García et al, 2021;Torres-Flores and Peña-Ortega, 2022). On the other hand, rTg4510 transgenic mice have been useful to analyze the pathophysiology of tauopathies (Ramsden et al, 2005;SantaCruz et al, 2005;Xolalpa-Cueva et al, 2022) and the interaction between Aβ and P-tau (Busche et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Once the skull was exposed, a hole was drilled with the following coordinates (from Bregma): −1 mm medio-lateral, −0.25 antero-posterior. A microinjector was gently introduced into the lateral ventricle (2.8 mm from the skull) and a total of 5 μL of either the Aβ oligomers solution (500 pmoles; Martínez-García et al, 2021) or its vehicle (F12 medium; Hernández-Soto et al, 2019) was injected at 0.5 μL/min with a Hamilton syringe. Martínez-García et al (2021) and Desbène et al (2012) have shown that this ICV dose of Aβ is enough to induce cognitive and neurophysiological alterations in mice (Desbène et al, 2012;Martínez-García et al, 2021).…”
Section: Surgery and Microinjectionmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations are linked to concomitant changes in glutamate and GABA that affect the excitatory and inhibitory balance of retinal circuits. Martinez-García et al [3] also describe alterations in piriform cortical excitability that may contribute to olfactory dysfunction in AD.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, both amyloid and tau generated animal models of AD exhibit neurodegeneration in olfactory regions and olfactory deficits (Cassano et al, 2011;Wesson et al, 2011;Saiz-Sanchez et al, 2012;Gandy et al, 2013;Kong et al, 2018;Adlimoghaddam et al, 2019;Ghosh et al, 2019). Several of these models point to PC specific dysfunction, due to increased expression of Aβ, tau and glycogen synthase kinase-3β in the PC compared to other odor sensory regions (Macknin et al, 2004;Cassano et al, 2011;Gandy et al, 2013), and direct disruption of PC function and PC-olfactory bulb (OB) coupling (Martinez-Garcia et al, 2021).…”
Section: Introductionmentioning
confidence: 99%